Educational interventions promoting modifiable lifestyle behaviours for cardiovascular disease in pre-registration nursing students: a scoping review - Creighton, Laura; Caughers, Gemma; Mitchell, Gary; McMahon, James; Neubeck, Lis; Fitzsimons, Donna (BMC nursing, 2025)
Aims Modifiable lifestyle behaviours, such as smoking and high alcohol consumption are more prevalent among pre-registration nursing students, than the general population. Embedding education on the impact of these risk factors for cardiovascular disease and motivating behaviour change is essential. This scoping review aims to investigate educational interventions promoting healthier lifestyle behaviours for cardiovascular disease prevention within the curriculum for pre-registration nursing students. Methods and results The methodological framework for scoping reviews was used to identify literature on educational interventions for pre-registration nursing students, focusing on smoking, nutrition, physical activity, and alcohol consumption as key modifiable risk factors for cardiovascular disease. Following the PRISMA-ScR Checklist, 1631 records were screened using predefined inclusion and exclusion criteria, resulting in 29 records for data extraction and analysis. Interventions varied by region: North America ( N = 7), Europe ( N = 11), Asia ( N = 8), and the Middle East ( N = 3). Most studies targeted smoking cessation ( N = 11), followed by nutrition ( N = 6), alcohol ( N = 3), or a combination of these ( N = 9). Findings indicate that educational interventions improved knowledge, self-efficacy, and led to behaviour changes, particularly in smoking cessation. Conclusion There are numerous educational interventions that aim to educate pre-registration nursing students about knowledge of modifiable lifestyle behaviours or supporting detrimental behaviour change in the clinical setting however, most interventions individually address a single behaviour such as smoking. This scoping review identifies that there is a paucity of educational interventions directly focused on cardiovascular disease prevention that encompass all four of the modifiable lifestyle behaviours of smoking, nutrition, physical activity and alcohol consumption in combination for pre-registration nursing students.